Retrospectives: Regulating banks versus managing liquidity: Jeremy bentham and henry thornton in 1802 - Berdell, John and Mondschean, Thomas (The Journal of Economic Perspectives)
At nearly the same moment, Jeremy Bentham and Henry Thornton adopted diametrically opposed approaches to stabilizing the financial system. Henry Thornton eloquently defended the Bank of England's actions as the lender of last resort and saw its discretionary management of liquidity as the key stabilizer of the credit system. In contrast, Jeremy Bentham advocated the imposition of strict bank regulations and examinations, without which, he predicted, Britain would soon experience a systemic crisis$1 (Bwhich he called "universal bankruptcy." There are strong parallels but also dramatic differences with our recent attempts to reduce systemic risk within financial systems. The Basel III bank regulatory framework effectively intertwines Bentham's and Thornton's diametrically opposed approaches to stabilizing banks. Yet Bentham's and Thornton's concerns regarding the stability of the wider financial system remain alive today due to financial innovation and the politics of responding to financial crises. - Reproduceds
Keywords: Banks; Depository Institutions; Micro Finance Institutions; Mortgages, Financial Institutions and Services, Government Policy and Regulation